The Cambridge guide to theatre (Cambridge Univ. Press, 1988)
The book covers the factual entries on major playwrights and works, important traditions, theories, companies, practitioners, venues and events; individual country entries on theatre from Africa, Asia, The Americas and Europe; historical information on the origins of popular theatre tradition including folk drama, street theatre and nummers plays; description and illustration of work of factors, directors and designers including stage lighting and sound